2013
DOI: 10.1111/codi.12304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of tissue carcinoembryonic antigen expression as ancillary to serum carcinoembryonic antigen concentration in patients curatively resected for colorectal cancer

Abstract: Tissue CEA expression is a prognostic factor in patients with colorectal cancer. Analysis of tissue CEA expression may be helpful in determining the clinical utility of serial measurements of serum CEA as surveillance in patients with curatively resected colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The role of carcinoembryonic antigen (CEA) as a robust predictor of long-term survival following resection of CRLM remains poorly defined [9,10,12,[18][19][20][21][22] . Among many patients, CEA can be an effective marker to monitor for recurrence, as well as to assess response to systemic therapy [18,21] .…”
Section: Preoperative Carcinoembryonic Antigen Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of carcinoembryonic antigen (CEA) as a robust predictor of long-term survival following resection of CRLM remains poorly defined [9,10,12,[18][19][20][21][22] . Among many patients, CEA can be an effective marker to monitor for recurrence, as well as to assess response to systemic therapy [18,21] .…”
Section: Preoperative Carcinoembryonic Antigen Levelmentioning
confidence: 99%
“…Other studies have similarly noted that preoperative CEA > 200 ng/mL was an independent factor of poor OS and disease specific survival (DSS), respectively [18,21] . In a one study, Park et al [19] looked at both tissue CEA and serum CEA concentration after resection for CRLM and noted that CEA expression was an independent prognostic factor for OS and DFS. Of note, patients with elevations in both tissue CEA expression and serum CEA had a worse OS and DFS compared with patients who had only one CEA category elevated [19] .…”
Section: Preoperative Carcinoembryonic Antigen Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study reported that the grade of CEA expression in cancer tissue is related to the serum CEA level [16]. Such inconsistent results may be attributed to methodological differences in the evaluation of the CEA expression grade in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a positive relation between CEA levels in cancer tissue and serum CEA levels [16], whereas others have found no relation between these variables [17,18,19,20]. Currently available findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%